Triangle of Sadness: Of Vulnerability and Michel Foucault's Subject-Power Concept - Özer, Beril (CINEJ cinema journal, 2025)
Foucault (1977a) analyzed the concept of power from a different perspective and defined power not only as a power relationship between people and states, but as a set of strategies that is omnipresent and comes to society from multiple domains. In the phenomenon of power constructed through discourses, each individual in interrelation continues their practices while getting influenced by the process. The concept of vulnerability refers to the inner impulse that guides the actions of individuals driven by the instinct for survival, as well as the sense of vulnerability that this impulse imposes on them. Dependence on others brings a sense of vulnerability also. In this study, which is based on Foucault's concepts of subject and power, the concept of vulnerability is studied in the context of Ruben Östlund’s award-winning film Triangle of Sadness, focusing on themes of power, the transformation of authority, interpersonal relations in everyday life and vulnerability. As a result of the analysis, it was concluded that gender roles and social statuses are indicators of power, individuals may experience a sense of vulnerability due to various weaknesses, the relationships between power and authority are always in a state of transformation, societal gender roles can change when the dynamics of power shift and that discourses are influential in the formation of the subject. In the analysis of the film Triangle of Sadness, critical discourse analysis, one of the qualitative research approaches, has been employed. The concept of vulnerability and Foucault’s notion of power were discussed prior to the film review.